SURVEY OF ATTITUDES ON THE END-USE EFFICIENCY OF PROMOTIONAL ACTIVITIES OF PRODUCERS STYROFOAM - Jovičić, Dragoljub; Vranješ, Marija; Gašević, Dragana (International Journal of Economic Practice and Policy, 2017)
More energy prices, on the one hand, and the increasing use of insulating materials in the construction industry, on the other hand, contributed to intensifying competition in the business market. In order to attract and retain a greater number of customers, manufacturers of styrofoam must constantly work on the quality of their offerings, and integrated marketing communications. In conditions when competitors offer a relatively homogeneous, right promotional activities have become one of the main factors of competitive advantage. The aim was to investigate the relative importance of certain promotional tools in marketing of styrofoam on the market of Vojvodina. In accordance with these goals were used value of the arithmetic mean, standard deviation and coefficient of variation at promotional instruments. Data were collected through unstructured personal communication with a sample of 20 of the respondents. The research results indicate that there is a very strong and positive impact of promotional activities on the placement of styrofoam. At the same time, by far the most powerful influence of the advertising, then personal selling, and sales promotion, and the last place relations with the public. These results indicate that none of the instruments of promotional mix should not be ignored, but also emphasize the need to focus on those instruments that are of major influence on the placement of styrofoam. In this way, the findings of this research can be of benefit management companies operating in the market of Vojvodina styrofoam.
Keywords: styrofoam market; personal selling; advertising; sales promotion; public relations